Non-R&D, interactive learning and economic performance: Revisiting innovation in small and medium enterprises - Jörg Thomä; Volker Zimmermann (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
In the present paper, various groups of innovating German SMEs are empirically identified according to their use (or non-use) of in-house R&D, their reliance on external sources of knowledge, and the degree of internal interactive learning that they employ.In order to account for non-R&D innovation activities, we apply the STI/DUI concept as a theoretical starting point. This distinguishes between (1) the science, technology, innovation (STI) mode with its strong emphasis on formal processes of in-house R&D and (2) the doing, using, interacting (DUI) mode with its focus on experience-based knowledge and interactive learning. On this basis, the empirical results indicate that three groups associated with different modes of learning and innovation exist within the German SME sector: the supplier-dependent DUI group, the customer-oriented DUI group and the STI/DUI group. The corresponding findings confirm that SMEs innovate differently depending on the specificities of their knowledge environments. In order to evaluate this in terms of innovation policy, we examine how these learning modes among innovating SMEs relate to overall company performance. Our main observation is that each learning mode is likely to positively affect performance, at least to some degree. There isno differ-ence in economic performance between the three learning modes as long as non-high-growth SMEs are considered. Hence, in large parts of the SME sector, it is economically rational to choose a non-R&D-oriented mode of learning and innovation. The paper con-cludes with some policy implications of these findings.
Keywords: M21; O32; O38; 330; Modes of learning; R&D; Non-R&D innovation; Interactive learning; SMEs